Association between parental separation, childhood trauma, neuroticism, and depression: a case control study - Sanwald, Simon; , GenEmo Research Group; Montag, Christian; Kiefer, Markus; Connemann, Bernhard J.; Schönfeldt-Lecuona, Carlos; Kammer, Thomas (Frontiers in Psychiatry, 2023)
Background Parental separation has been suggested to be associated with depression development in offspring. The new family constellation subsequent to separation could be associated with elevated scores of childhood trauma, shaping more emotionally instable personalities. This could ultimately be a risk factor for mood disorders and particularly the development of depression in life. Methods To test this hypothesis, we investigated the associations between parental separation, childhood trauma (CTQ) and personality (NEO-FFI) in a sample of N = 119 patients diagnosed with depression and N = 119 age and sex matched healthy controls. Results While parental separation was associated with elevated scores of childhood trauma, there was no association between parental separation and Neuroticism. Furthermore, in a logistic regression analysis, Neuroticism and childhood trauma were found to be significant predictors for depression diagnosis (yes/no), but not parental separation (yes/no). Conclusion Parental separation might be associated with depression only indirectly via childhood trauma. Childhood trauma or Neuroticism seem more directly related to the development of depression. However, it is worthwhile to install prevention programs helping parents and children to cope with parental separation in order to minimize the impact of separation and associated stressors.